Development, implementation and evaluation of high-quality virtual preoperative anaesthetic assessment during COVID-19 and beyond: a quality improvement report. Issue 4 (10th October 2022) - Popivanov, Petar; Bampoe, Sohail; Tan, Terry; Rafferty, Paul
Abstract : Background: Preoperative risk factor identification and optimisation are widely accepted as the gold standard of care for elective surgery and are essential for reducing morbidity and mortality. COVID-19 public health restrictions required a careful balance between ensuring best medical practices and maintaining safety by minimising patient face-to-face attendance in the hospital. Based on the successful implementation of telemedicine (TM) in other medical specialties and its feasibility in the preoperative context, this study aimed to develop, implement and evaluate a high-quality virtual preoperative anaesthetic assessment process. Methods: The three-step model for improvement was used. The specific, measurable, actionable, relevant, time aim (step 1) and measures for improvement (step 2) were defined at the onset of the project. The plan–do–study–act tool was used for the structured implementation of improvement interventions (step 3) in three phases. Data relating to virtual and in-person referrals, assessments, did-not-attend (DNA) rate, consultation time, day of surgery delays and cancellations, and service-user and provider experience surveys were recorded prospectively. Results: A total of 2805 patients were assessed in the preoperative anaesthetic assessment clinic between July 2020 and March 2021. The mean rate of virtual preoperative assessments was 50% (SD ±10) (1390/2805). 0.1% (30/2805) were inappropriately referred on the alternative pathway. The DNA rate was 0.4% (8/1398) and 3% (43/1458) for virtual and in-person pathways, respectively. The mean consultation times for virtual and in-person attendance were 19 (SD ±7) and 31 (SD ±13) min, respectively. There were five same-day surgery cancellations and one delay due to medical reasons. When asked about their experience with the virtual assessment, both service users and providers reported high satisfaction, minimal technical difficulties and shared concerns about limited opportunities for physical examination. Conclusion: This is one of the first implementational studies to comprehensively outline the feasibility of TM in preoperative anaesthetic assessment during COVID-19.